Importancia de la metodología abc (activity- based-costing) para mejorar la rentabilidad en el Hotel Gran Americano. - Espinoza Zambrano, Maria Jose; Carrion Garcia, Byron Fernando (Machala : Universidad Técnica de Machala, 2025)
The main objective of this research is to analyze the importance of the ABC (Activity-Based Costing) methodology to improve the profitability of Hotel Gran Americano. In a highly competitive environment such as the hospitality sector, having accurate cost allocation systems is essential for effective decision-making. Through a descriptive study with a quantitative approach, the current cost structure of the hotel was evaluated, and the implementation of activity-based costing was proposed as a strategic tool. The results show that the ABC methodology allows for a more accurate identification of indirect costs and their proper assignment to the services provided, generating a clearer view of profitability by activity. Consequently, its application would significantly contribute to optimizing resources, reducing unnecessary expenses, and strengthening the hotel’s competitiveness in the market.
La presente investigación tiene como objetivo principal analizar la importancia de la metodología ABC (Activity-Based Costing) para mejorar la rentabilidad del Hotel Gran Americano. En un entorno altamente competitivo como el sector hotelero, contar con sistemas precisos de asignación de costos resulta fundamental para una adecuada toma de decisiones. A través de un estudio descriptivo con enfoque cuantitativo, se evaluó la estructura de costos actuales del hotel y se propuso la implementación del costeo basado en actividades como herramienta estratégica. Los resultados evidencian que la metodología ABC permite identificar con mayor exactitud los costos indirectos y asignarlos correctamente a los servicios prestados, lo que genera una visión más clara de la rentabilidad por actividad. En consecuencia, su aplicación contribuiría significativamente a optimizar recursos, reducir gastos innecesarios y fortalecer la competitividad del hotel en el mercado.
Keywords: METODOLOGÍA ABC; RENTABILIDAD; GESTIÓN DE COSTOS; HOTELERIA